2005
DOI: 10.1111/j.1439-0450.2005.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Brucellosis, Tularemia, and Yersiniosis in Wild Boars (Sus scrofa) from North‐Eastern Germany

Abstract: Brucellosis and tularemia are classical zoonotic diseases transmitted from an animal reservoir to humans. Both, wildlife and domestic animals, contribute to the spreading of these zoonoses. The surveillance of the animal health status is strictly regulated for domestic animals, whereas systematic disease monitoring in wildlife does not exist. The aim of the present study was to provide data on the prevalence of anti-Brucella, anti-Francisella and anti-Yersinia antibodies in wild boars from North-Eastern German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 38 publications
(77 reference statements)
8
77
3
5
Order By: Relevance
“…09%) in sera from the years 1976-1989 [32,33] as well as more recently in boars (3 . 1% in 1995/1996) [13]. To the south-west of Brandenburg in Thuringia, F. tularensis has recently been isolated from a hare and in the western neighbouring state, Saxony-Anhalt, we reported a ticktransmitted human tularaemia [21,34].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…09%) in sera from the years 1976-1989 [32,33] as well as more recently in boars (3 . 1% in 1995/1996) [13]. To the south-west of Brandenburg in Thuringia, F. tularensis has recently been isolated from a hare and in the western neighbouring state, Saxony-Anhalt, we reported a ticktransmitted human tularaemia [21,34].…”
Section: Discussionmentioning
confidence: 95%
“…Two previous studies in the north of Germany revealed the absence of F. tularensis antibodies in hares [12] but a seroprevalence of 3 . 5% in wild boars [13]. For the present study we used the standard methods, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However these species are not considered to be particularly susceptible to developing disease. Their potential role as asymptomatic carriers, shedding and/or spreading the infection in nature, has not been investigated [1,7,9,89,90].…”
Section: Sources Of Infection and Routes Of Disseminationmentioning
confidence: 99%
“…These species might therefore serve as useful indicators for the presence of tularemia in areas where small mammals are infected. Furthermore, they can be used for serological surveillance of trends in tularemia and for the detection of spread of the pathogen to new geographical areas [7,9,10,89,90]. Serology in hares has been used for wildlife surveillance of tularemia in Hungary [34], where results from regular testing of hunted hares for almost three decades has identified variation in prevalence of the pathogen over time in different parts of the country.…”
Section: Surveillance Of Wildlife and Humansmentioning
confidence: 99%
“…Al Dahouk et al (2005) found that 22 per cent of wild boar sera in Germany were seropositive. RuizFons et al (2006) showed that approximately 10 per cent of young adults and 28 per cent of adult wild boars in open estates in southern Spain were seropositive for brucellosis.…”
Section: Bacteria In Wild Boars That Are Potentially Transmissible Tomentioning
confidence: 99%